SERVICE RESPONSIVENESS AND VOLUNTEERISM OF RURAL WOMEN IN RIVERS STATE (American Journal of Research in Humanities and Social Sciences, 2024)
The aim of this research was to determine the extent to which service responsive responsiveness influences volunteerism among rural women in Rivers State. In the course of fulfilling this purpose, the study empirically examined the relationship between service responsiveness and two of the attributes of volunteerism which were utilization and recognition. The study adopted the quasi-experimental design; and questionnaire was the instrument used to collect the primary data. Four hundred questionnaires were distributed to rural women in Rivers State. Data gotten was analyzed and the two hypotheses raised, thus, indicating two moderate positive rank correlation. We concluded that volunteerism to an extent can be influenced by service responsiveness, we also recommend that organizations and the government should put more effort to discover and satisfy the needs of the volunteers in order to increase their performance and retain them.